6r-(r+3)=10-(7-5r)

Simple and best practice solution for 6r-(r+3)=10-(7-5r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r-(r+3)=10-(7-5r) equation:


Simplifying
6r + -1(r + 3) = 10 + -1(7 + -5r)

Reorder the terms:
6r + -1(3 + r) = 10 + -1(7 + -5r)
6r + (3 * -1 + r * -1) = 10 + -1(7 + -5r)
6r + (-3 + -1r) = 10 + -1(7 + -5r)

Reorder the terms:
-3 + 6r + -1r = 10 + -1(7 + -5r)

Combine like terms: 6r + -1r = 5r
-3 + 5r = 10 + -1(7 + -5r)
-3 + 5r = 10 + (7 * -1 + -5r * -1)
-3 + 5r = 10 + (-7 + 5r)

Combine like terms: 10 + -7 = 3
-3 + 5r = 3 + 5r

Add '-5r' to each side of the equation.
-3 + 5r + -5r = 3 + 5r + -5r

Combine like terms: 5r + -5r = 0
-3 + 0 = 3 + 5r + -5r
-3 = 3 + 5r + -5r

Combine like terms: 5r + -5r = 0
-3 = 3 + 0
-3 = 3

Solving
-3 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7v/8=21 | | X/4-x/12=2 | | 2x-y+z=-11 | | -1+2x=28+13 | | t/6-2=11 | | kx-3=5 | | u/7=17.92 | | P=344x-560 | | 8v=20.40 | | 3n+8+12n-5-7n+11= | | X-11/2=9 | | 7x=2/3 | | 8/1=.22/n | | 1/7(-21x-2) | | 3x+88=14x | | 6q-4=2q-12 | | 56=9w-w | | 20k-11=9k-99 | | 1-2x^2/sinx | | x/4-4=3 | | 180-120.4= | | 6x-1=16-51 | | 8r+15=95 | | a+bi=-9i+4i | | 7(23.2)-42= | | a+bi=9i+4i | | ((2/3x)^1/3)-((10/3x)^-2/3)=0 | | 25(r-2)=320(r-4) | | z^2-(4-6i)z-4-12i=0 | | 3x-4iy=-9y+i(5+x) | | 4q-2q=4-12 | | fx=(7-3x)(3x+7) |

Equations solver categories